Evaluation of potential reserves of production for melting synthetic iron - Зрайченко-Полозенцев, Алексей Владимирович; Коваль, Оксана Сергеевна; Дёмин, Дмитрий Александрович (Technology audit and production reserves, 2011)
The article describes the use of intellectual research methodology of large systems (IRMLS) for experimental data of industrial production batches of synthetic iron and synthesis based on the results of optimal chemical composition of cast iron with a given set of mechanical properties